The Effect of Stock Trading Volume, Leverage, and Dividend Policy on Stock Price Volatility - Maulana, Yasir; Rismawati, Dede; Disman; Dodi (Asosiasi Ahli Administrasi Indonesia, 2025)
This paper intends to explore how trading volume, financial leverage, and dividend distribution strategies influence fluctuations in stock prices. The study utilized a quantitative approach, incorporating both descriptive and verification analyses. Out of 44 listed companies, a purposive sampling technique yielded a sample of 12 firms observed over a five-year timeframe. Findings reveal that trading volume, leverage, and dividend policy collectively contribute to stock price variability. Moreover, each of these variables individually exerts a positive and statistically significant impact. These insights may serve as a reference for prospective investors considering equity investments, highlighting the importance of understanding price volatility to anticipate market trends. Recognizing these fluctuation patterns enables more informed and strategic investment decisions, while also helping investors to manage potential financial risks effectively.